EXTERNAL TRADE OF ROMANIA – TEN YEARS AFTER EU ACCESION (2007- 2016) - Florentina Viorica GHEORGHE (Challenges of the Knowledge Society)
Advantages of the EU single market and the costs related to adaptation the Community context and requirements, the impact of the international economic and financial crisis and the difficultiesin accessing EU Structural and Social Cohesion Funds are among the major factors that have influenced the economic evolution of Romania in the period 2007-2016, including the external trade in goods. There have been changes in the structure of Romania's external trade, determined, on the one hand, by the accession to the EU, and on the other hand, by the impact of the international economic crisis started in 2008. The way in which the Romanian external trade has responded to the aforementioned factors is analyzed in this paper, on the basis of the following criteria: the evolution of specific indicators to the field of foreign exchanges of goods, in the year 2016 as compared to the year 2007; the magnitude of the economic downturn in 2009 and 2010 years as a result of the negative impact of the crisis; the decline recovery in years; resilient economic sectors. International comparisons are used in order to evaluate the position of Romania as against the neighboring EU Member States as well as its main EU trading partners in the context of the EU integration process.